THE EFFECT OF THE PICTURE AND PICTURE LEARNING MODEL ON THE SHORT STORY WRITING SKILLS OF GRADE IV STUDENTS OF SD NEGERI SUKAHARJA 1, TANGERANG REGENCY - Nisa Ayudhiya; Ina Magdalena; Yayah Huliatunisa (PIONIR: JURNAL PENDIDIKAN, 2024)
This research aims to find out whether there are differences in short story writing skills between students who were given the picture and picture learning model and students who were given the conventional learning model in class IV students at SDN Sukaharja 1, Tangerang Regency. This research uses a quasi-experimental research method with a non-equivalent control group design. The population subjects in this study were class IV students at SDN Sukaharja 1 Tangerang Regency, taking a sample of two classes totaling 54 students, namely class IV A totaling 27 students as the experimental class and class IV B totaling 27 students as the control class. Data collection techniques using short story writing skills test instruments, observation, interviews and documentation. To test the pretest hypothesis in this study using the t test, from the t test results obtained tcount = 1.8658 and ttable = 2.0066, this difference of 0.1408 shows that the tcount value is slightly lower than ttable, it can be concluded that there is no difference in results between the experimental class and the control class. Meanwhile, for testing the posttest hypothesis, the results of the t test obtained tcount = 11.3936 and ttable = 2.0066, so it can be concluded that the picture and picture learning model has an influence on the short story writing skills of class IV students at SDN Sukaharja 1, Tangerang Regency.Keywords: Picture and Picture Learning Model, Short Story Writing Skills